Burden of Parents in Children with Disability at Sekolah Luar Biasa Negeri Cileunyi - Yusi Desriyani; Ikeu Nurhidayah; Fanny Adistie (Faculty of Nursing, Universitas Jember, 2019)
Children with disabilities are children who have limited whether physical, intellectual, mental, sensory, and multiple disability. Children with disabilities tend to have poor quality of life due to low ability fulfilled basic needs independently. Therefore, they need special treatment from their parents and that could be the reasons of burden for parents as primary caregiver. This research aims to find the general burden of parents in disabilities children who attended Sekolah Luar Biasa (SLB) Negeri Cileunyi. This is a quantitative descriptive research with cross sectional approach. The population in this research were 158 parents (father/mother) of children with disability. The sample in this research was obtained 67 people by using convenience sampling technique. The research used Zarit Burden Interview (ZBI) as research instrument. The data have been obtained and analyzed by univariate analysis. The results will be analyzed by using frequency distribution. The result showed that 46.3% means little or no burden, 37.3% means mild to moderate burden, 14,9% means moderate to severe burden and 1,5% means severe burden. The conclusions of this research show that almost half of respondents are in the category of little or no burden. However, there were still respondents who had a severe burden, this is due to parents and children characteristics, poor self-control and lack of social support. Nurses need to provide family center care such as counseling and providing health education to parents with disabilities children and optimize existing support groups.